THE DEVELOPMENT OF A DIGITAL TRANSFORMATION LEADERSHIP MODEL FOR EXECUTIVES OF AUTONOMOUS UNIVERSITIES IN SOUTHERN THAILAND - Kaewjomnong, Aniwat; Nilsook, Prachyanun; Chatakan , Werayut (Journal of MCU Nakhondhat, 2026)
The objectives of this research were: 1) To analyze the components of digital transformation leadership; 2) To develop a model of digital transformation leadership; and 3) To Examine and evaluate the model of digital transformation leadership for executives of autonomous universities in Southern. This study employed a research and development approach. The quantitative phase involved a sample of 400 personnel from three autonomous universities in Southern, selected through stratified random sampling. The research instrument was a questionnaire with a reliability coefficient of .957. The statistical techniques included test of variable relationship, Bartlett’s Test of Sphericity, eigenvalues, percentage of variance, and cumulative variance. The qualitative phase involved nine key informants who were personnel from autonomous universities in Southern, selected through purposive sampling. The research instruments included connoisseurship and focus group discussions, and analyzed using content analysis. The findings revealed that digital transformation leadership of university administrators consisted of eight components: digital-driven agility, digital culture development, digital literacy and competency, strategic resource and investment management, digital communication and ethical use of digital technologies, global digital branding and networking, visionary thinking and digital strategy, and outcomes of digital transformation. When developing an accurate and appropriate digital transformation leadership model for executives, consist of 6 components: the model’s name, principles, objectives, elements, implementation process, and conditions for success. Regarding the validation and evaluation of the digital transformation leadership model for executives, it was found to be both feasible and beneficial.